“El modelo constructivista para la enseñanza aprendizaje en la asignatura de Ciencias Naturales " - Tapia Marín, Darío Samuel (2022)
At present, in the teaching-learning process, it is required that the learning achieved by the students be significant, so it is necessary to give an adequate approach to said process, however, some teachers still practice with traditionalist models that they do not allow significant learning, hence it is important that teachers are very clear about the pedagogical models based on constructivism, and apply it in the classroom, in such a way that the student is not a simple spectator, but also an actor in the process. teaching-learning process of Natural Sciences. In this sense, the general objective of the present work is to diagnose the application of the constructivist pedagogical model in the subject of Natural Sciences, through direct research in the students of the seventh grade of Basic General Education in the Félix Valencia Educational Unit, Joseguango parish. Bajo, Latacunga Canton, in the year 2022. In carrying out this work, the inductive method was used, being a qualitative-quantitative, descriptive and field research, since the research was done in the aforementioned institution. For data collection, the guides of questions to the authority and the teacher, and a survey applied to the students were used. From the results obtained, a constructivist pedagogical model is not applied in its entirety, evidencing that there are a number of students who are not satisfied with the way in which the activities are carried out in class in said subject.